Non-Linear Regression on the Number of Stunting Cases in Central Java in 2023 - Syasya Qonita Azizah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Chronic nutritional problems, namely stunting, have a major impact on physical growth and development of children, especially in Central Java. Central Java Province is one of the regions with the highest number of stunting in Indonesia, reaching 20.7% in 2023. This study used data from the 2023 Central Java Health Profile. This study aims to analyze the relationship between factors that cause stunting, including access to proper sanitation, complete basic immunization, underweight, exclusive breastfeeding, maternal health services K4, maternal health services K6, completion of basic education, and Consumption of Blood Supplement Tablets to the number of stunting cases in Central Java. The analysis used the Generalized Linear Model (GLM) and Integrated Nested Laplace Approximation (INLA) approaches with three distributions, namely Poisson, Gaussian, and Negative Binomial distributions. Negative Binomial Model. The Negative Binomial distribution proved to be the best model in analyzing stunting data in Central Java based on the smallest values in AIC, BIC, dan DIC. Based on the analysis results obtained, the percentage of underweight in toddlers shows a significant influence on the number of stunting cases in Central Java.